Pengaruh Frekuensi Penyiraman Terhadap Pertumbuhan dan Hasil Sawi Pakcoy (Brassica rapa subsp.chinensis) - Ignatius Endito Nugroho; Theresa Dwi Kurnia (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2025)
The irrigation system is regulated based on the frequency of watering, where water is given in the right amount at the right time. Water flows directly around the plant roots and the soil surface continuously and gradually. The purpose of this study was to determine the effect of watering frequency on the growth and yield of pakcoy mustard greens and to determine the watering frequency that produces the best growth and yield.This research was conducted from May to July 2024 at the Salaran Experimental Garden, Faculty of Agriculture and Business. This study applied seven watering treatments with different times: morning watering (P1), afternoon watering (P2), evening watering (P3), morning and afternoon watering (P4), morning and afternoon watering (P5), afternoon and afternoon watering (P6), morning, afternoon, and afternoon watering (P7). This study used 3 repetitions for each treatment, so the total number of experimental units was 21. This research method uses a Randomized Block Design (RBD), the results are analyzed using analysis of variance (ANOVA), then further tested using DMRT with a confidence level of 5%. Based on the research results, the frequency of watering did not have a significant effect on the growth or yield of pakcoy mustard plants. Meanwhile, the best watering frequency treatment was obtained by treatments P5 and P7.